CD44+ fibroblasts increases breast cancer cell survival and drug resistance via IGF2BP3‐CD44‐IGF2 signalling. Issue 9 (18th May 2017) - Liu, Yonglei; Yu, Conghui; Wu, Yonggang; Sun, Xiangjun; Su, Quanping; You, Cuiping; Xin, Hongwu
Abstract: CD44, a cell adhesion protein, involves in various process in cancer such as cell survival and metastasis. Most researches on CD44 in cancer focus on cancer cells. Recently, it is found that CD44 expression is high in fibroblasts of tumour microenvironment. However, its role in communication between fibroblasts and breast cancer cells is seldom known. In this study, CD44‐positive (CD44 + Fbs) and CD44‐negative carcinoma‐associated fibroblasts (CD44 − Fbs) were isolated and cocultured with breast cancer cells for analysis of cell survival and drug resistance. We found that CD44 + Fbs promoted breast cancer cell survival and paclitaxel resistance and inhibited paclitaxel‐induced apoptosis. Our further research for the molecular mechanism showed that IGF2BP3 bound to CD44 mRNA and enhanced CD44 expression, which increased IGF2 levels of fibroblasts and then stimulated breast cancer cell proliferation and drug resistance. IGF2 was found to activate Hedgehog signal pathway in breast cancer cells. In conclusion, the results illustrated that in CD44 + Fbs, binding of IGF2BP3 and CD44 promotes IGF2 expression and then accelerates breast cancer cell proliferation, survival and induced chemotherapy resistance likely by activating Hedgehog signal pathways.